THE INFLUENCE OF CEO CHARACTERISTIC AND COMPENSATION TO EFFECTIVE TAX RATE WITH CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Wati Wati; Christina Dwi Astuti (Jurnal Magister Akuntansi Trisakti, 2017)
The aim of this research is to analyze the influence of characteristic and CEO compensation (CEO compensation and CEO stock ownership) to effective tax rate with corporate governance as moderating variable. The type of this research is quantitative, and done in Bursa Efek IndonesiaPopulation in this research are manufacture companies that listed in Indonesia Stock Exchange during the study period of years 2012-2016.The samples of this research using purposive sampling method are 76  companies. Multiple regression is statistic method which is used to test the research hypothesis. Testing of hypotheses using SPSS 23.The results of this research show that CEO compensation and corporate governance significantly positive influence the effective tax rate while CEO characteristic and CEO stock ownership have not influence the effective tax rate. Corporate governance not able to moderate relation between CEO characteristic, CEO compensation and CEO ownership to effective tax rate.